An approach to norms assimilation in normative multi-agent systems - Mahmoud M.A.; Ahmad M.S.; Ahmad A.; Yusoff M.Z.M.; Mustapha A.; Hamid N.H.A. (Springer Verlag, 2023)
Empirical researches on norms have become the subject of interest for many researchers in norms and normative systems. However, research in norms assimilation seems to be lacking in concept and theory within this research domain. In this paper, we propose a norms assimilation theory and implement such assimilation by exploiting an agent's internal and external beliefs. Internal belief represents the agent's ability while the external belief refers to the assimilation cost with a specific social group or society. From the agent's beliefs of its ability and assimilation cost, it is able to decide whether to accept or reject assimilation with a particular social group. This paper builds an approach to norms assimilation and analyzes the cases for an agent to decide to assimilate with a social group's norms. © Springer International Publishing Switzerland 2014.